Combination of both primary pure squamous cell carcinoma (SCC) and conventional invasive lobular carcinoma (ILC) in the same breast; A rare case report and review of the literature - Ola A. Harb; Taha A. Baiomy; Mohamed I. Abdelhamid; Loay M. Gertallah; Ahmed A. Obaya; Mohammad Abd Alkhalik Basha (Elsevier, 2019)
Background: Squamous cell carcinoma (SCC) of the breast is a rare primary breast cancer, while invasive lobular carcinoma (ILC) is the commonest special subtype of breast cancer. Combination of primary SSC and ILC of the breast is extremely rare and up to our knowledge no reported case about such combination.Case:Herein we have reported a very rare case of combination between primary SCC and ILC of the breast in a 51 year old post menaupausal female patient and review of the literature.Aim; due to rarity of such condition and uncertain treatment modality it should be kept in mind its presence to allow choosing adequate therapy. Conclusion: Primary pure SCC of the breast is a rare malignancy which has a rapid rate of growth and a poor prognosis, moreover, ILC has high metastatic rate. Due to rarity of such condition and uncertain treatment modality it should be kept in mind its presence to allow choosing adequate therapy. Keywords: Breast, Squamous cell carcinoma (SCC), Invasive lobular carcinoma (ILC)